Resettlement features of population of Ternopil oblast in the context of new administrative and territorial system - Наталія Заблотовська; Ольга Данілова; Михайло Салій (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The study is devoted to the study of territorial differences in the resettlement of the population of Ternopil oblast after the introduction of changes in the administrative-territorial structure of the oblast, as one of the oblast regions where the boundaries and centers of the new administrative raions practically coincided with their eponymous inter-district resettlement systems. After all, as a result of the change in the administrative-territorial system, we received a certain redistribution of the population within the basic units of resettlement systems, and they are the beginning of those irreversible changes in resettlement systems that we will observe in the coming years. The article calculates and analyzes indicators-characteristics of population placement at the level of territorial communities of the oblast. The author uses the indicators of area of administrative units and their population, population density, the average distance between settlements, the coefficient of urbanization and the share of the urban population, the population concentration index and the degree of development of connections between the centers of territorial communities, as an indicator of the future prospects of cooperation between newly formed administrative centers.